Hubungan Faktor Resiko Dengan Kejadian Eklampsia Pada Ibu Hamil di RSUD Ambarawa - Nur Cahyani Ari Lestari; Syahrida Wahyu Utami; Reni Rahayu (JOURNAL EDUCATIONAL OF NURSING(JEN), 2019)
Eclampsia is a pregnancy-specific syndrome in the form of decreased organ perfusion due to vasospasm and endothelial activation, characterized by increased blood pressure, proteinuria, with or without edema accompanied by seizures. Eclampsia can harm the mother and fetus. The exact cause of eclampsia is unknown, but eclampsia can be triggered by several risk factors including the age of too young or too young, nulliparous, obesity in pregnancy, chronic hypertension, diabetes and multiple pregnancies. This study aims to determine the relationship between risk factors and the incidence of eclampsia in pregnant women in Ambarawa Hospital. The research method used was descriptive analytic research with a cross-sectional approach. Research variables included age, parity, obesity, chronic hypertension, diabetes, twin pregnancies as risk factors for eclampsia and eclampsia. The study population was all pregnant women in Ambarawa General Hospital in January-June of 896 people. The research sample was taken using the proportionate stratified random sampling technique that was in accordance with the inclusion and exclusion criteria as many as 90 people. The results showed that pregnant women aged between 20-35 years were 49 people (54.4%), the parity of pregnant women was nulliparous as many as 37 people (41.1%), pregnant women were not obese as many as 72 people (80%) and not experiencing chronic hypertension as many as 70 people (77.8%), almost all pregnant women did not suffer from diabetes as many as 86 people (95.6%) and did not experience twin pregnancies as many as 83 people (92.2%). Risk factors associated with pre-eclampsia events included parity (p value 0.033), obesity (p value 0.017), chronic hypertension (p value 0,000) and diabetes (p value 0.041. The most dominant risk factor after multivariate regression analysis logistics is chronic hypertension, it is recommended for health workers and the public to prevent the occurrence of pre-eclampsia, especially for mothers who have risk factors. Keywords: Risk Factors, Incidence of Eclampsia